2021
DOI: 10.1186/s12911-020-01378-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of nursing students following the implementation of comprehensive computer-based nursing process in medical surgical internship: a quasi-experimental study

Abstract: Background The nursing process is the core and the standard of practice in nursing profession. Nowadays, the use of information technology in the field of nursing processes, education and practice has been emphasized. Since nurse’s attitudes towards clinical information systems are considered as an indicator of the success rate of information systems, and nurse’s attitudes about the nursing process can affect their execution of the process. So the purpose of this study was to evaluate nursing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Por otro lado, la aplicación de lenguajes estandarizados representa una mejora de las habilidades cognitivas del 91.8%, mientras que para el 8,2% no fue asi. Estos hallazgos son semejantes a los obtenidos por Parvan et al,(2021) quienes estudiaron las actitudes de los estudiantes ante la implementación del proceso de forma computarizada sus datos mostraron puntuaciones altas con respecto al empleo del mismo, en concordancia con este estudio.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otro lado, la aplicación de lenguajes estandarizados representa una mejora de las habilidades cognitivas del 91.8%, mientras que para el 8,2% no fue asi. Estos hallazgos son semejantes a los obtenidos por Parvan et al,(2021) quienes estudiaron las actitudes de los estudiantes ante la implementación del proceso de forma computarizada sus datos mostraron puntuaciones altas con respecto al empleo del mismo, en concordancia con este estudio.…”
Section: Discussionunclassified
“…Por otro lado, todas las áreas del desarrollo humano y científico requieren disponer de procesos estandarizados y científicamente probados a los cuales se les conoce actualmente como información basada en evidencia (Parvan et al, 2021). En tal sentido la aplicación de las taxonomías en el desarrollo de la práctica pre-profesional de los internos de Enfermería es una necesidad imperiosa, se ha demostrado que los aprendizajes, habilidades y aptitudes que se adquieren durante la formación profesional marcan el desenvolvimiento y desempeño en las actividades concretas de los profesionales (NANDA Internacional, 2021).…”
Section: Introduciónunclassified
“…The nursing process has gained acceptance globally, and while registered nurses (RNs) agree on its beneficial effects, it is not widely used in practice [ 12 , 13 ] due to a lack of competence among RNs [ 14 ]. One reason the widespread use of the nursing process has not emerged is that nurses lack competence and, consequently, lack confidence in their ability to use it [ 15 , 16 ]. Applying the nursing process is connected to critical thinking and goal-oriented tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the nursing process is an important indicator covering a high proportion of guidance and evaluation areas in clinical practice education, it is reported that nursing students still have difficulties in the clinical application of this process. In other words, the significance of the nursing process in clinical practice has been emphasized, but specific efforts for improvement remain insufficient ( Bayram et al, 2022 ; Keiffer, 2018 ; Melin-Johansson et al, 2017 ; Parvan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%